Tribological Properties and Oil Flow Observation of Porous Sintered Metal with Dimple Texturing by Block-on-Disk Friction Tester - Ayako Omura (Japanese Society of Tribologists, 2019)
Presence of micrometer-scale textures on a surface can modify the friction properties of that surface. In this study, we investigated the fundamental tribological properties of Cu-Sn porous sintered metal with the rounded rectangle dimple texturing under hydrodynamic lubrications. The results of block-on-disk tribological tests and in-situ oil flow observations revealed that the presence of dimple texturing on the sliding surface increases the friction coefficient of porous specimens. From the visualization of oil effused regions on porous surfaces, it was observed that the position of the maximum peak of oil film pressure distribution is shifted toward the outlet direction of oil flow as a result of dimple texturing. In case of porous sintered metal, addition of dimple texturing enhanced the absorbance of lubricating oil into the interconnected pores and caused a reduction in the oil film thickness.